Pengaruh pemberian Air Jeruk Lemon Terhadap Mual Muntah Pada Ibu Hamil Trimester I di PMB Bidan Nining Karawang Tahun 2023 - Siregar, Renince; Tyas, Fitria Prawartining; Siamanjuntak, Farida M (Jurnal Ayurveda Medistra, 2024)
Background: Nausea-vomiting during pregnancy often occurs caused by an increase in the hormones of estrogen, progesterone and hormone human chorionic gonadotropin (HCG) which causes the pregnant women is experiencing body weakness, paleness, and the daily activity is disrupted, decreased appetite until the mother weight is loss, malnutrition the pregnant women also experiencing dehydration to the point where a nutritional deficit occurs which endangers the condition of the mother and fetus. Lemon water contains ingredients good enough in reducing Morning Sickness in pregnant women. This study aims to determine the effect of lemon juice on nausea and vomiting in first trimester pregnant women in PMB’s midwives Nining in the District of Karawang since August to September 2023.Methodology: The method used in this research is a quasi-experiment study using a one group pre-post test design on 15 respondents from 20 populations. The intervention was carried out for 7 (seven) days to assess the frequency of vomiting between pre and post intervention. Data were analyzed using SPSS version 25.0 for the Paired Samples Test.